The Effect Of Competency Development And Work Flexibility On Employee Productivity With Artificial Intelligence In Performance Evaluation As A Moderating Variable At PT Cybertrend Intrabuana - Kusuma, Kiki Andriani; Iqbal, M. Ali (IJOSMAS, 2025)
Abstract - This research aims to examine the influence of: (1) competency development on employee productivity, (2) work flexibility on employee productivity, (3) the moderating role of artificial intelligence in performance evaluation on the relationship between competency development and employee productivity, and (4) the moderating role of artificial intelligence in performance evaluation on the relationship between work flexibility and employee productivity at PT Cybertrend Intrabuana. PT Cybertrend Intrabuana is a company operating in the field of data science and artificial intelligence. The object of this research is the employees working at PT Cybertrend Intrabuana, located in Jakarta. The study involved 83 respondents using a descriptive quantitative approach. Therefore, the data analysis method employed in this study is SEM-PLS through questionnaires. This research shows that competency development has a positive and significant effect on employee productivity, work flexibility has a positive and significant effect on employee productivity, and artificial intelligence in performance evaluation is able to moderate the relationship between competency development and employee productivity. furthermore, artificial intelligence in performance evaluation is unable to moderate the relationship between work flexibility and employee productivity.